Place of the Journal of Turkish Librarianship in Publishing World - Doğan Atılgan (Türk Kütüphaneciliği)
One of the most important activities of professional associations is to contribute in life long learning facilities oftheir members through publications. Turkish Lib- rarians’ Association has started such contribution since three years af ter its fo- undation. The Journal of Turkish Librarianship (JTL) with its professional and scholarly contents has been the most significant information source for the Turkish librarians during the last 50 years. JTL became an international and a pe- er-reviewed Journal without changing its publ ication frequency which w as determined at the beginning. This particular study showed that there is a correlation between the covered subjects and development stages of Turkish librarianship. This paper examines JTL’s evolving phases and its development, and the subject titles covered by JTL from the beginning to present.